Enhanced Cementation of Co2+ and Ni2+ from Sulfate and Chloride Solutions Using Aluminum as an Electron Donor and Conductive Particles as an Electron Pathway - Sanghyeon Choi; Sanghee Jeon; Ilhwan Park; Mayumi Ito; Naoki Hiroyoshi (Metals, 2021)
Cobalt and nickel have become important strategic resources because they are widely used for renewable energy technologies and rechargeable battery production. Cementation, an electrochemical deposition of noble metal ions using a less noble metal as an electron donor, is an important option to recover Co and Ni from dilute aqueous solutions of these metal ions. In this study, cementation experiments for recovering Co2+ and Ni2+ from sulfate and chloride solutions (pH = 4) were conducted at 298 K using Al powder as electron donor, and the effects of additives such as activated carbon (AC), TiO2, and SiO2 powders on the cementation efficiency were investigated. Without additives, cementation efficiencies of Co2+ and Ni2+ were almost zero in both sulfate and chloride solutions, mainly because of the presence of an aluminum oxide layer (Al2O3) on an Al surface, which inhibits electron transfer from Al to the metal ions. Addition of nonconductor (SiO2) did not affect the cementation efficiencies of Co2+ and Ni2+ using Al as electron donor, while addition of (semi)conductors such as AC or TiO2 enhanced the cementation efficiencies significantly. The results of surface analysis (Auger electron spectroscopy) for the cementation products when using TiO2/Al mixture showed that Co and Ni were deposited on TiO2 particles attached on the Al surface. This result suggests that conductors such as TiO2 act as an electron pathway from Al to Co2+ and Ni2+, even when an Al oxide layer covered on an Al surface.